The importance of urban heritage in supporting cultural tourism - Al-Tabali, Jumaa; Al-Zaidi, Naeem (Al-Adab Journal, 2019)
Urban heritage is a cultural wealth representing the identity of peoples and nations, reflecting the story of human the development of civilization through history. It is an economic resource that contributes to the support of national income by stimulating foreign and domestic tourism. Urban heritage areas have become attractions in our world today and an important economic resource for tourism, recreation, promenade and recreation, which creates a sustainable development, reflected positively in the economic and social benefits of local communities and contribute to the increase and diversity of sources of national income, by creating investment opportunities in urban heritage areas.